8x-3(3x+4)=11

Simple and best practice solution for 8x-3(3x+4)=11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-3(3x+4)=11 equation:


Simplifying
8x + -3(3x + 4) = 11

Reorder the terms:
8x + -3(4 + 3x) = 11
8x + (4 * -3 + 3x * -3) = 11
8x + (-12 + -9x) = 11

Reorder the terms:
-12 + 8x + -9x = 11

Combine like terms: 8x + -9x = -1x
-12 + -1x = 11

Solving
-12 + -1x = 11

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -1x = 11 + 12

Combine like terms: -12 + 12 = 0
0 + -1x = 11 + 12
-1x = 11 + 12

Combine like terms: 11 + 12 = 23
-1x = 23

Divide each side by '-1'.
x = -23

Simplifying
x = -23

See similar equations:

| x^2+x-15=0 | | 7k+2=4k-25 | | 5x+9=8x+33 | | 4y-7=8y-23 | | 7h-6=2h-21 | | 2p+3=p-4 | | 123+3= | | 2p+3=-4 | | 8x+5=14-x | | 5+6x=25+x | | 12-6=8p-2 | | 7d=-2-18 | | 3a=20-2a | | 7d-2=-2 | | 4y-7=-3 | | 2(x-3)+5(x+2)=4(x-1)+3 | | 4m+1=-3 | | 4-3(2x+5)=5-(x-3) | | 12x+y=16 | | 2(x+21)=5x+21 | | 3(x+2)+2x=5x-2(x-4) | | 40-3x=17x | | 12p-6=8p-2 | | 4x+3x-4=3x+8 | | 7h+4=4h-5 | | 8x-2x+4=2x | | [10(3*x)+x]+[3x+10x]=88 | | 7d=-2d-18 | | 9x^2-225= | | 2x(2x-10)=-30+6x | | 2x-5(4-x)+3=14-(-5+2x) | | (2x^2+5x)(20x^2-7x-3)=0 |

Equations solver categories